﻿The genome of the egg parasitoid Trissolcus basalis (Wollaston) (Hymenoptera, Scelionidae), a model organism and biocontrol agent of stink bugs - Zachary Lahey; Huayan Chen; Mark Dowton; Andrew D. Austin; Norman F. Johnson (Journal of Hymenoptera Research, 2023)
Trissolcus basalis (Wollaston) is a minute parasitic wasp that develops in the eggs of stink bugs. Over the past 30 years, Tr. basalis has become a model organism for studying host finding, patch defense behavior, and chemical ecology. As an entry point to better understand the molecular basis of these factors, in addition to filling a critical gap in the genomic resources available for parasitic Hymenoptera, we sequenced and assembled the genome of Tr. basalis using short (454, Illumina) and long read (Oxford Nanopore) sequencing technologies. The three sequencing methods produced 32 million reads (4.10 Gb; 27.9×), which were assembled into 7,586 scaffolds. The 147 Mb (N50: 42.8 kb) assembly contains complete sequences for 93.1% of the insect BUSCO dataset, and an extensive annotation protocol resulted in 14,158 protein-coding gene models, 12,197 (86%) of which had a blast hit in GenBank. Repetitive elements comprised 13.8% of the genome, and a phylogenomic analysis recovered Tr. basalis as sister to Chalcidoidea, a result in line with other studies. We identified 174 rapidly evolving gene families in Tr. basalis, including olfactory receptors and pheromone/general odorant binding proteins. These genetic elements are an obligatory portion of the parasitoid-host relationship, and the draft genome of Tr. basalis has and will continue to be useful in elucidating these relationships at finer resolution.